The NLRP3 inflammasome in age-related eye disease: Evidence-based connexin hemichannel therapeutics. (February 2022) - Mugisho, Odunayo O.; Green, Colin R.
Abstract: The inflammasome pathway is a fundamental component of the innate immune system, playing a key role especially in chronic age-related eye diseases (AREDs). The inflammasome is of particular interest because it is a common disease pathway that once instigated, can amplify and perpetuate itself leading to chronic inflammation. With aging, it becomes more difficult to shut down inflammation after an insult but the common pathway means that a shared solution may be feasible that could be effective across multiple disease indications. This review focusses on the NLRP3 inflammasome, the most studied and characterized inflammasome in the eye. It describes the two-step signalling required for NLRP3 inflammasome complex activation, and provides evidence for its role in AREDs. In the final section, the article gives an overview of potential NLRP3 inflammasome targeting therapies, before presenting evidence for connexin hemichannel regulators as upstream blockers of inflammasome activation. These have shown therapeutic efficacy in multiple ocular disease models. Highlights: The NLRP3 inflammasome plays an important role in age-related eye disease. NLRP3 inflammasome complex assembly requires two signals, priming and activation. Proposed therapies target either inflammasome activation or complex assembly. ATP is an activation signal that has attracted the most interest in recent years. Connexin43 hemichannel blockers prevent ocular ATP-dependent inflammasome activation.